Controlled synthesis of α-MnO2 nanowires and their catalytic performance for toluene combustion. (March 2016) - Cheng, Gao; Yu, Lin; Lan, Bang; Sun, Ming; Lin, Ting; Fu, Zhiwei; Su, Xiaohui; Qiu, Minqiao; Guo, Canhui; Xu, Bin
Graphical abstract: α-MnO2 nanowires with a length about 6–10 μm and an average diameter of 20 nm were synthesized through a facile and environment-benign hydrothermal route without any templates or surfactants. Highlights: One-dimensional α-MnO2 nanowires were prepared by a facile hydrothermal route. Shape and crystal phase of the products were controlled by tuning reaction conditions. A possible formation mechanism of the α-MnO2 nanowires was discussed. The α-MnO2 nanowires showed great catalytic activity for toluene combustion. Abstract: α-MnO2 nanowires with a length about 6–10 μm and an average diameter of 20 nm were synthesized through a facile hydrothermal process without any templates or surfactants. The products were characterized by X-ray powder diffraction, Raman spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, hydrogen temperature-programmed reduction techniques, X-ray photoelectron spectroscopy and surface area analysis. The effects of the hydrothermal temperature and the concentration of CH3 COOH on the crystal phase and morphology of the final products were studied in detail. The hydrothermal temperature and the concentration of CH3 COOH play crucial roles in determining the crystal phase and morphology of the products. The possible formation mechanism of the α-MnO2 nanowires was investigated and discussed. Additionally, the as-prepared α-MnO2 nanowires showed higher catalytic activity for toluene combustion than the commercial MnO2, suggesting their potential applications in the elimination of volatile organic compounds.